Purification and exclusion of sources in libraries and information centers (Journal of the College of Basic Education, 2023)
The study aims to develop a plan to purify and exclude sources that do not meet the needs of beneficiaries in the Central Library, after identifying the reality of cultural materials in it, identifying the obstacles facing this process and ways to address them, and forming a committee with competence and objective experience to contribute to this process and to have a An effective impact on the selection process by evaluating the collection periodically and effectively using the survey method, where the study sample books (two books) were selected from each main section of the Dewey Decimal Classification and then examined in terms of the number and dates of their loan and years of publication with their arrival in the library and numbers The dates of its registration to check it with the records and its application numbers to check it with the general index cards and the shelf index through observation, interview and field coexistence. As for the most important results, the library lacks the policies of group development, purification and exclusion with places to save it, and there is no study to evaluate the group. As for the most important recommendations, it is to prepare a policy for the selection and development of the collection with consideration of the proposed plan and the formation of a committee to select the collection and be itself in purifying and excluding it and benefiting from applying the plan to the library’s other collection of books (such as periodicals, theses, disks, etc.).